2018
DOI: 10.1155/2018/6821387
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Mechanism of ShiZhiFang on Uric Acid Metabolism in Hyperuricemic Rats

Abstract: Objective To explore the effect and mechanism of ShiZhiFang on uric acid metabolism. Methods 40 rats were divided into normal group, model group, ShiZhiFang group, and benzbromarone group. The hyperuricemic rat model was induced by yeast gavage at 15 g/kg and potassium oxonate intraperitoneal injection at 600 mg/kg for two weeks. During the next two weeks, ShiZhiFang group rats were given ShiZhiFang by gavage, and benzbromarone group rats were given benzbromarone by gavage. The serum uric acid, creatinine, blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
2
4
1
Order By: Relevance
“…The ShiZhiFang (SZF), a TCM formula which consists of plantago seeds/ Plantago asiatica L. (60 g), white mustard seeds/ Sinapis alba L. (30 g), vaccaria seeds/ Gypsophila vaccaria (L.) Sm 30 g, and abutilon seeds/ Malva verticillata L. (30 g), is a compound that our research group usually applied to the treatment of hyperuricemia and hyperuricemia-related diseases, such as urate nephropathy. The clinical efficacy and safety of lowering uric acid levels were confirmed in our previous clinical study [ 53 ]. In our later study to test the efficacy and mechanism of this formula upon metabolism of uric acid, we found that SZF may be involved in facilitating the transcription as well as expression of renal rOAT3 and rOAT1 and inhibiting serum XOD activity [ 53 ].…”
Section: Herbs That Reduce Uric Acid By Inhibiting Its Production and Enhancing Its Excretionsupporting
confidence: 57%
See 1 more Smart Citation
“…The ShiZhiFang (SZF), a TCM formula which consists of plantago seeds/ Plantago asiatica L. (60 g), white mustard seeds/ Sinapis alba L. (30 g), vaccaria seeds/ Gypsophila vaccaria (L.) Sm 30 g, and abutilon seeds/ Malva verticillata L. (30 g), is a compound that our research group usually applied to the treatment of hyperuricemia and hyperuricemia-related diseases, such as urate nephropathy. The clinical efficacy and safety of lowering uric acid levels were confirmed in our previous clinical study [ 53 ]. In our later study to test the efficacy and mechanism of this formula upon metabolism of uric acid, we found that SZF may be involved in facilitating the transcription as well as expression of renal rOAT3 and rOAT1 and inhibiting serum XOD activity [ 53 ].…”
Section: Herbs That Reduce Uric Acid By Inhibiting Its Production and Enhancing Its Excretionsupporting
confidence: 57%
“…The clinical efficacy and safety of lowering uric acid levels were confirmed in our previous clinical study [ 53 ]. In our later study to test the efficacy and mechanism of this formula upon metabolism of uric acid, we found that SZF may be involved in facilitating the transcription as well as expression of renal rOAT3 and rOAT1 and inhibiting serum XOD activity [ 53 ].…”
Section: Herbs That Reduce Uric Acid By Inhibiting Its Production and Enhancing Its Excretionsupporting
confidence: 57%
“…Scientists suggested that inflammatory necrosis is associated with an innate immune response and sterile injury can also activate the innate immune system leading to unnecessary damage in normal tissue (Rock et al, 2010). Recently (Wu et al, 2018), it was realized that the activation of NLRP3 inflammasome promoted the secretion of IL-1β and IL-18 as well as triggered a new cell death which resulted from inflammation. Pyroptosis is an example of cell inflammatory necrosis which is characterized by the formation of a ruptured pore with a diameter ranging between 1.1 and 2.4 nm in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that gout-associated uric acid crystals stimulate GSDMD, which is dispensable for cell death as well as IL-1β release (Rashidi et al, 2019). From our previous study, it was evident that the renal tubules led to inflammatory injury via NLRP3 inflammasome activation (Wu et al, 2017) besides uric acid transporter down-regulation (Wu et al, 2018), in hyperuricemic kidneys. However, the knowledge on whether uric acid result in renal tubular epithelial cell pyroptosis is scanty.…”
Section: Introductionmentioning
confidence: 99%
“…The serum lipid peroxidation level was measured as described elsewhere (Samarghandian et al 2014). The serum levels of uric acid and nitric oxide (NO) were determined by calorimetric assay (Wu et al 2018;Van Beezooijen et al 1998). The serum levels of ceruloplasmin, zinc, copper, PGE 2 , MMP-3, TNF-α, IL-1β, and IL-6 were determined as described previously (Dai et al 2018).…”
Section: Biochemical Markersmentioning
confidence: 99%